Responsive and proactive market orientation and innovation success under market and technological turbulence - Bodlaj, Mateja; Coenders, Germa; Zabkar, Vesna (Journal of Business Economics and Management, 2012)
The study investigates how market and technological changes in an organization’s business environment moderate the relationships between responsive and proactive market orientation, innovation success, and market success of the organization. The respondents in the study were senior managers of companies operating in a Central European country. The Internet survey resulted in 441 usable questionnaires. Data were analyzed using a non-linear structural equation models with MPLUS5. The results provide support for distinguishing between the two complementary forms of market orientation, proactive and responsive. While proactive market orientation is a determinant of both innovation and market success of the organization, the impact of responsive market orientation on the innovation and market success is positive and significant only in a rapidly changing market environment. Companies can improve their innovation success and in turn market success by improving their proactive market orientation, i.e. by investing resources in exploring customer needs, customer problems with existing products and latent customer needs. The study contributes to the literature by examining the entire chain of relationships between market orientation, innovation success and market success by adopting both a responsive and proactive market orientation. It is the first study that examines these relationships in the context of companies from a European country and with consideration of market turbulence/changes.